Using Mobile Augmented Reality to Tactically Re-Encounter, Re-Create, and Re-Appropriate Public Spaces - Liao, Tony Chung Li; Humphreys, Lee (AoIR Selected Papers of Internet Research, 2013)
As augmented reality (AR) is becoming technologically possible and publicly available through mobile smartphone and tablet devices, there has been relatively little empirical research studying how people are utilizing mobile AR technologies and forming social practices around mobile AR. This study looks at how mobile AR is mediating the everyday practices of urban life, and how users are deploying it to shape their relationship and interpretations of places around them. Through qualitative interviews with users of Layar, a mobile AR browser, we found several emerging uses. First, users are navigating with these tools to experience place in ways that are distinct from other location based services. Second, we found a growing segment of users creating content for Layar that aims to communicate about and through place, historicize and challenge the meanings of place, and assert their own narratives of place through their augmentations.